2006
DOI: 10.1002/da.20215
|View full text |Cite
|
Sign up to set email alerts
|

Do anxiety and depression cluster into distinct groups?: a test of tripartite model predictions in a community sample of youth

Abstract: Because of their high comorbidity and strong associations, the distinctiveness of anxiety and depression in youth continues to be debated. In this study we used cluster analysis in a community sample (n=225) of youth to test tripartite model predictions regarding the grouping of individuals based on their levels of anxiety and depression symptoms. Findings were consistent with tripartite model predictions that four groups would emerge (primarily elevated on anxiety symptoms only, elevated on depression symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 29 publications
6
50
0
Order By: Relevance
“…Given current conceptualizations of the disorders, Clark and Watson [1] proposed that negative affect would be common to both anxiety and depression but that low positive affective experience would be distinctly related to depression whereas physiological hyperarousal would be uniquely correlated with anxiety. Clark and Watson found strong support for their model with adults, and later research found mixed support for the general model with children [2,[32][33][34][35]. For example, in a group of psychiatric inpatient youth, negative affect was related to both anxiety and depression whereas lack of positive affect was related to depression.…”
Section: Frequency Of Negative and Positive Affectmentioning
confidence: 99%
“…Given current conceptualizations of the disorders, Clark and Watson [1] proposed that negative affect would be common to both anxiety and depression but that low positive affective experience would be distinctly related to depression whereas physiological hyperarousal would be uniquely correlated with anxiety. Clark and Watson found strong support for their model with adults, and later research found mixed support for the general model with children [2,[32][33][34][35]. For example, in a group of psychiatric inpatient youth, negative affect was related to both anxiety and depression whereas lack of positive affect was related to depression.…”
Section: Frequency Of Negative and Positive Affectmentioning
confidence: 99%
“…Measures of anxiety and depression in children and adolescents have repeatedly been found to correlate strongly [1][2][3][4]. Likewise, diagnosis-based generalized anxiety disorder and major depressive disorder are found to have high levels of comorbidity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, symptom scales have identified combined symptoms of anxiety and depression, or internalizing problems, as an important emotional syndrome in childhood and adolescence [8], and some research has supported a one-factor model of anxiety and depression [9]. Nevertheless, previous studies of the structure of anxiety and depression in children and adolescents have found inconsistent levels of construct overlap [2,3,10]. Moreover, other research suggests two-factor [11] or three-factor [12] models of anxiety and depression, and that these constructs tend to cluster in distinct groups [2,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent research has supported the utility of all three constructs in children and adolescents in clinical (Joiner, Catanzaro, & Laurent, 1996;Joiner & Lonigan, 2000;Lonigan, Carey, & Finch, 1994) and nonclinical (Cannon & Weems, 2006;Olino, Klein, Lewinsohn, Rohde, & Seeley, 2007;Phillips, Lonigan, Driscoll, & Hooe, 2002) settings.…”
mentioning
confidence: 98%